Late palaeozoic magmatism in the basement rocks Southwest of Mt. Olympos, Central Pelagonian zone, Greece: Remnants of a permo-carboniferous magmatic arc - REISCHMANN, T.; KOSTOPOULOS, D. K.; LOOS, S.; ANDERS, B.; AVGERINAS, A.; SKLAVOUNOS, S. A. (Bulletin of the Geological Society of Greece, 2001)
We dated basement rocks from several localities southwest of Mt. Olympos, as well as from a locality near the top of the mountain using the single zircon Pb/Pb evaporation technique. For the samples southwest of the mountain, the ages obtained range from ca. 280 to 290 Ma, with only a few zircon grains being around 300 Ma. By contrast, the sample from near the top of the mountain appears to be slightly younger, with ca. 270 Ma. These ages imply that the granitoids crystallized during Late Carboniferous - Early Permian times, and are therefore younger than the basement gneisses of other regions of the Pelagonian zone, which yielded zircon ages of around 300 Ma (e.g. Yarwood & Aftalion 1976, Mountrakis 1983, De Bono 1998, Engel & Reischmann 2001). However, the ages obtained in the present study are identical, within error, to the muscovite Ar-Ar cooling ages from Mt. Ossa (Lips 1998). Our geochronological data show that the magmatic evolution for this part of the basement of the Pelagonian Zone lasted at least 30 Ma.